2010
DOI: 10.1001/archdermatol.2010.161
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Skindex-Teen, a Quality-of-Life Instrument for Adolescents With Skin Disease

Abstract: Setting: Academic pediatric dermatology practice. Patients: A total of 205 patients between the ages of 12 and 17 years with a skin condition. Main Outcome Measures: Participants completed the Skindex-Teen questionnaire, reported sociodemographic data, and answered clinical questions at enrollment. Four weeks later, they completed Skindex-Teen and responded to clinical questions again. Forty patients also completed Skindex-Teen 48 hours after baseline. Results: Of 205 patients, 200 (97.6%) completed all enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 18 publications
2
59
0
1
Order By: Relevance
“…The overall score can be broken down into two subscales pertaining to physical symptoms (5 items) and psychosocial function (16 items). The validation study by Smidt et al [40] confirmed strong face validity and test-retest reliability at 4 weeks by looking at 205 dermatological patients from ages 12 to 17 years (mean age 15.3 ± 1.4 years); 11 of the patients had psoriasis who reported impairment in physical symptoms, especially itching and pain, appearance and impact on clothing choices, self-esteem and self-image [31,40] . Unfortunately, to these authors' knowledge this questionnaire has not appeared in many other publications.…”
Section: Skindex-teenmentioning
confidence: 90%
“…The overall score can be broken down into two subscales pertaining to physical symptoms (5 items) and psychosocial function (16 items). The validation study by Smidt et al [40] confirmed strong face validity and test-retest reliability at 4 weeks by looking at 205 dermatological patients from ages 12 to 17 years (mean age 15.3 ± 1.4 years); 11 of the patients had psoriasis who reported impairment in physical symptoms, especially itching and pain, appearance and impact on clothing choices, self-esteem and self-image [31,40] . Unfortunately, to these authors' knowledge this questionnaire has not appeared in many other publications.…”
Section: Skindex-teenmentioning
confidence: 90%
“…We decided to develop a specific Family Burden Ichthyosis questionnaire (“FBI”) according to the rigorous methodology of construction of QoL questionnaires (Figure 1) by two steps: creation of the questionnaire and validation [17-19]. This methodology required a multidisciplinary team involved in the care of the patients and their families.…”
Section: Methodsmentioning
confidence: 99%
“…It remains the only dermatology-specific QoL instrument for this age group. Two dermatology-specific instruments for adolescents with skin diseases were developed [19, 20] but have not yet been used in other published studies. Several disease-specific instruments (predominantly atopic dermatitis-specific) for children and their parents were developed.…”
Section: Hrqol Assessment In Children With Skin Diseasesmentioning
confidence: 99%